?IMPACT OF COPPER VAPOUR CONTAMINATION ON ARGON ARCS? (Biological Sciences - PJSIR, 1995)
A fast, accurate and comprehensive emission spectroscopic set-up has been employed to study the impactof coppervapour on an Ar-Cu mixture plasma. Temperature profiles in the arc have been determined in the absence ofCu vapourand then in its presence, using the absolute line intensity method for an Ar spectral line; these profiles have beencompared with temperature profiles derived from relative intensities of Cu I lines. Temperature profiles derived fromrelative intensity ofCu I lines have been used to calculate the radial density distribution of copper atoms in the arc. Thefollowing observations have been made from the resulting atomic number densities: (i) the copper vapour concentratesin the fringes of the arc, with atomic number densities up to 8.6 X 1011 (cm'): and (ii) Cu atomic number densities in thecore of the arc are small.